Spinal meningioma surgery in octogenarians: functional outcomes and complications over a 2-year follow-up period - Lenga, Pavlina; Gülec, Gelo; Bajwa, Awais Akbar; Issa, Mohammed; Kiening, Karl; Ishak, Basem; Unterberg, Andreas (Medicina, 2022)
Background and Objectives: Population aging in industrial nations has led to an increased prevalence of benign spinal tumors, such as spinal meningiomas (SMs), in the elderly. The leading symptom of SM is local pain, and the diagnosis is confirmed after acute neurological decline. However, little is known about the optimal treatment for this frail patient group. Therefore, this study sought to assess the clinical outcome, morbidity, and mortality of octogenarians with SMs and progressive neurological decline undergoing surgery and to determine potential risk factors for complications. Materials and Methods: Electronic medical records dated between September 2005 and December 2020 from a single institution were retrieved. Data on patient demographics, neurological conditions, functional status, degree of disability, surgical characteristics, complications, hospital course, and 90-day mortality were collected. Results: Thirty patients aged ≥80 years who were diagnosed with SMs underwent posterior decompression via laminectomy and microsurgical tumor resection. The patients presented with a poor baseline history (mean CCI 8.9 ± 1.6 points). Almost all SMs were located in the thoracic spine (n = 25; 83.3%). Progressive preoperative neurological decline was observed in 21/30 (n = 21; 70%) patients with McCormick Scores (mMCS) ≥3, and their mean motor score (MS) was 85.9 ± 12.3. in the in-hospital and 90-day mortality rates were 6.7% and 10.0%, respectively. The MS (93.6 ± 8.3) and mMCS (1.8 ± 0.9) improved significantly postoperatively (p < 0.05). The unique risk factor for complications was the severity of comorbidities. Conclusions: Decompressive laminectomy and tumor removal in octogenarians with progressive neurological decline improved patient functional outcomes at discharge. Surgery seems to be the “state of the art” treatment for symptomatic SMs in elderly patients, even those with poor preoperative clinical and neurologic conditions, whenever there is an acceptable risk from an anesthesiological point of view.
Gesehen am 21.12.2022